Principal’s Leadership in Realizing Pancasila Student Profile - Kusuma, Rukma Deny; Kristiawan, Muhammad; Fitria, Happy (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the leadership of the head of SMA LTI IGM Palembang and the implementation of in learning in realizing the profile of Pancasila students. To achieve this goal, a qualitative approach was used. Data were collected by using interview, documentation, and observation. The results showed that the principal conducted planning, implementation, and evaluation of the character of Pancasila students in the school as a whole. The principal has a commendable character and is able to implement it in carrying out his duties and functions as an educator, manager, administrator, supervisor, leader, innovator, and motivator; as well as being an example and role model for all educators and education personnel. In the implementation of realizing the profile of Pancasila students through learning both subject learning and Pancasila student recruitment projects.